URGENSI PENERAPAN KEDISIPLINAN PADA PESERTA DIDIK DALAM BELAJAR DI LINGKUNGAN SEKOLAH - Rusnawati; Nufiar (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2022)
Discipline is a very important factor in learning at school. For this reason, students are required to behave according to the rules and regulations that apply in school. But the willingness and willingness to comply with the discipline, there are still those who do not have the awareness to obey the rules, students feel heavy because they do not know the benefits and uses. Action is needed in schools in carrying out and realizing discipline. Based on these problems, the formulation of the problem in this study is how is the discipline of learning in schools. How are the factors that influence discipline in learning at the school. And how is the urgency of discipline in learning at school. To be able to answer the problems that have been formulated, the authors use a qualitative approach with the method of literature review. From the results of the study, it can be concluded that discipline in learning is a series of attitudes, behavior of students who show obedience and obedience to study regularly at school. Discipline is not something that happens automatically or spontaneously to a person, but the attitude is formed on the basis of several factors that influence it. The factors that affect the discipline that exists in students include innate factors, self-awareness, interest and motivation, mindset, exemplary, advice, training, family environment, school and groups in interaction. Discipline education is very important given to schools to educate students, this is done so that students can easily understand and obey immediately, to carry out their obligations in learning and directly understand the prohibitions. Understand good and bad behavior. Learn to control desires and do things without feeling threatened by punishment by the rules at school.